ANALYSIS OF LANDSAT 8 SATELLITE IMAGERY TO IDENTIFY POTENTIAL OF SPRING (Case Study: District Bojonegoro) - Sukojo, Bangun Muljo; Aristiwijaya, Bayu (GEOID, 2016)
By integrating remote sensing technology to the analysis of Landsat 8 satellite imagery to identify, is expected to provide solutions and services in a repeated and continuous monitoring with wide regional coverage. Exploration of water resources needs to be done in order to meet community needs.Bojonegoro known as districts often experience water shortages in some regions of sub-section, especially during the dry season. Action in the form of research on the potential presence of springs made as early action in an effort to identify and search for the source of water to meet the needs of society.From the science of remote sensing, identification of potential springs do with observations of vegetation density of processed Landsat 8 satellite image, especially the image output May to September 2014. The data supporting the use of topographic data is like a river network, land cover and hipsografi. Efforts to use data validation geology and hydrogeology. From this research, it was found that Bojonegoro can be divided into four classes of potential, ie High, Medium, Low and Rare. The potential emergence of springs identified in the area of the plateau with prolific aquifer truncated by faults geology. Geographic information system is used as a tool in the process of spatial analysis is the conclusion that would be the magnitude of the correlation between the size of the vegetation density to the size of the potential presence of springs.